Influence of Social Media Advertising Experience on Affect, Intrusiveness and Recall: Moderating Role of Platform - Manala-O, Safa (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2022)
Social media advertising is now regarded as a necessary tool for brands to reach their consumers. Recent global reports disclose that companies are allotting billions of US Dollars for social media advertising on platforms such as Facebook, Youtube and Instagram. It is commonly thought that all social media platforms are experienced similarly, however new studies have shown that each platform is uniquely consumed and that affects how advertisements are perceived. This study examined the significant relationships among advertising experience, affect, intrusiveness and recall to determine their interrelation in the context of social media. It also examined the moderating effect of social media platform on these relationships. Findings reveal that advertising experience has a direct and an indirect influence through affect on advertisement recall. Social media platform was also found to significantly moderate this link. Intrusiveness was not found to be relevant. Findings of this study are crucial for companies to know that advertising across social media platforms does not yield the same, or even successful, outcomes in terms of advertisement recall. Some platforms are more likely to yield better advertisement recall because of how they are experienced by users and that affects the way they view and think about advertisements.